Iterative schemes with some control conditions for a family of finite nonexpansive mappings in Banach spaces. Issue 2 (30th June 2005) - Jung, Jong Soo; Cho, Yeol Je; Agarwal, R. P.
Abstract : The iterative schemes with some control conditions for a family of finite nonexpansive mappings are established in a Banach space. The main theorem improves results of Jung and Kim (also Bauschke). Our results also improve the corresponding results of Cho et al., Shioji and Takahashi, Xu, and Zhou et al. in certain Banach spaces and of Lions, O'Hara et al., and Wittmann in a framework of a Hilbert space, respectively.